PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SIKAP RELIGIUS SISWA MELALUI KEGIATAN EKSTRAKURIKULER IPNU IPPNU DI MADRASAH ALIYAH MUALIMIN MUALIMAT REMBANG - Novitasari , Dwi; Saefudin, Ahmad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers and identify supporting and inhibiting factors of the role of Islamic Religious Education (PAI) teachers in improving students' religious attitudes through IPNU and IPPNU extracurricular activities at Madrasah Aliyah Mualimin Mualimat Rembang. This study uses a qualitative approach of case study type, with data collection techniques using interviews and documentation, data analysis techniques according to Miles and Huberman through the stages of data reduction, data presentation and drawing conclusions. This study reveals that PAI teachers act as mentors, motivators, and role models in religious activities. These extracurricular activities have proven effective in shaping students' religious character and increasing their understanding of religious teachings. However, there are challenges in implementing the role of teachers, such as limited time and the support needed. This study reveals that the active participation of PAI teachers in extracurricular activities is crucial to achieving the desired goals of religious education.